The great Syrian revolt and the rise of Arab nationalism - Provence, Michael, 1966- (Modern Middle East series (Austin, Tex.), 2005)
"A history of the largest and longest-lasting people's revolt in the Arab East, which attempted to liberate Syria from French Mandate rule in 1925"--Provided by publisher.